If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(9n-1)+7(n=6)=-60
We move all terms to the left:
2(9n-1)+7(n-(6))=0
We multiply parentheses
18n+7n-2-42=0
We add all the numbers together, and all the variables
25n-44=0
We move all terms containing n to the left, all other terms to the right
25n=44
n=44/25
n=1+19/25
| 3x(4)–6=4x | | 1/4y-3=1/3 | | (15x+5)+120=22x+4 | | 6=7u | | 3n+15n-2n+-8n+-5=-13 | | q-52=21 | | 1/6(12y+18)-9=-1/5(5y-45) | | h-28=11 | | 3x=-6+6=5+6 | | -7/4w-3=5/3w+7/4 | | h-83=-45 | | 14=5+m | | -2x+6(-2x+22)=62 | | h-483=-45 | | p+3p+0.2p=180 | | y=-1.4=-2.7 | | 41=z-23 | | 6y-4=2y+16 | | 2(2x)^(1/2)+1=(4x+1)^(1/2) | | X^2+20x+100=11 | | −10(x−7)−7(x+2)=0 | | 5x+7-3x=8+x+7 | | -5/2w-1=15 | | 13u+-11u-15=9 | | 22x-3=60 | | -6/v=-2 | | 0.2(2x+0.5)=5(0.5-2) | | 7+4x=10x-6 | | 3x-4(-3x-6)=-66 | | 2/3x-1=-1/3x-7 | | 4=(-0.8)x | | 6=m-7÷8 |